Physical Activity Time and Intensity in Physical Education During the COVID-19 Pandemic. Issue 3 (June 2022) - Lourenço, Joana; Rodrigues, Catarina; Flôres, Fábio; Soares, Denise
With the COVID-19 outbreak, schools have experienced difficulty providing moderate-to-vigorous physical activity (MVPA) to their students, which should normally account for at least 50% of children's physical education (PE) class time. We aimed to determine the intensity of physical activity (PA) within PE classes at various grade levels to compare children's in-class PA with the World Health Organization's (WHO) recommended guidelines. Thus, 301 students (1st to 12th grade) participated in the investigation. Children were evaluated during the PE classes with different typologies and durations. We assessed PA intensity using accelerometry and grouped data into either sedentary-to-light PA (SEDLI) or MVPA. Each child was assessed using both the time spent in PA (hours:minutes:seconds) and the percentage of time spent in PA versus other class activities. We found that, in the second-grade level group (fifth and sixth grades), girls spent more time in MVPA intensity than boys. Additionally, two-hour PE classes doubled the SEDLI for students in the third-grade group, and polythematic classes (those with more than one sport) promoted more MVPA level time than monothematic classes (only one sport). Concerning PA intensity during PE classes, 31–43% of the PE class total time was spent in MVPA but presented short duration and did not usually persist for 10 consecutive minutes (59% of the time). Children spent a large amount of time at the SEDLI intensity, considered insufficient for PA health benefits. Finally, to meet WHO guidelines for PA intensity, PE classes will need to increase MVPA time and reduce non-active periods between activities.